An Ayurvedic Preventive And Curative Approach To Periodontitis / Pyorrhea - Narang, Priyanka; Oommen, Sara Moncy (International Research Journal of Ayurveda & Yoga, 2021)
Oral diseases are one of the major health problem world-wide. Most of the oral diseases are due to bacterial infestation. In Periodontitis or pyorrhea, the tissues surrounding and supporting the teeth i.e periodontium is affected which causes bleeding red swollen gums, bad breath with bad taste and painful mobile teeth. The global need for alternative prevention and treatment options for oral diseases that are safe, effective and economical comes from the rise in disease incidence (particularly in developing countries), increased resistance by pathogenic bactAyurvedic treatment is aimed at patient as an organic whole and treatment consists of salubrious use of drugs, diets and certain practices. Many ayurvedic medicinal plants and formulations confer considerable anti-microbial activity against various microorganisms including bacteria’s responsible for pyorrhea, dental caries etc. This review article is mainly focused on the different Ayurvedic drugs, formulations and daily regimen effective in Periodontitis or pyorrhea. eria to currently used antibiotics and chemotherapeutics, opportunistic infections in immune-compromised individuals and financial considerations in developing countries.